2014
DOI: 10.1007/s10753-014-9995-x
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Inhibit COX-1 and COX-2 Enzymes and Cytokine/Chemokine Production in Human Whole Blood

Abstract: Cyclooxygenase 2 (COX-2) and the production of cytokines/chemokines are important targets for the modulation of the inflammatory response. Although a large variety of inhibitors of these pathways have been commercialized, some of those inhibitors present severe side effects, governing the search for new molecules, as alternative anti-inflammatory agents. This study was undertaken to study an hitherto not evaluated group of flavonoids, concerning its capacity to inhibit COX-1 and COX-2 enzymes, as well as to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 50 publications
4
84
0
7
Order By: Relevance
“…Indeed, xanthones 2c (not active) and 3b (holding three hydroxy groups) and xanthone 3c (with four hydroxy groups) did not reach an IC 50 at all. These data are corroborated by Ribeiro et al that previously found in structuralsimilar compounds, the less substituted flavonoids were those presenting a higher inhibitory activity [22]. This is the first paper that reports the inhibition of COX-1 activity by 2,3-diarylxanthones, but there are a few studies that explore the inhibitory capacity of other substituted xanthones using different experimental conditions.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Indeed, xanthones 2c (not active) and 3b (holding three hydroxy groups) and xanthone 3c (with four hydroxy groups) did not reach an IC 50 at all. These data are corroborated by Ribeiro et al that previously found in structuralsimilar compounds, the less substituted flavonoids were those presenting a higher inhibitory activity [22]. This is the first paper that reports the inhibition of COX-1 activity by 2,3-diarylxanthones, but there are a few studies that explore the inhibitory capacity of other substituted xanthones using different experimental conditions.…”
Section: Discussionsupporting
confidence: 81%
“…The human whole-blood assay to assess the COX-1 inhibition was performed as previously reported [21,22]. Collected blood (500 μL) was placed in microtubes and incubated in a water bath at 37°C with TXBSI (1 μM) and the tested xanthones (0.312-100 μM) dissolved in DMSO for 15 min.…”
Section: Cox-1 Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…COX-1 and COX-2 play critical roles during the transformation of arachidonic acid in prostaglandins [27, 28]. The overexpression of COX2 and prostaglandin is generated by several pro-inflammatory mediators, such as IL-1, IL-6, and TNF-α, and is related to fibrosis encapsulation, scar formation, and delayed wound healing [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are different non-steroidal anti-inflammatory drugs such as celecoxib and indomethacin that block COX2 and create an anti-inflammatory effect [31, 32]. In addition to this, other natural compounds, such as flavonoids, have been tested to reduce cytokine production and inhibit COX2 overproduction [28]. …”
Section: Introductionmentioning
confidence: 99%